The iPad & iPad Mini pocket guide - Carlson, Jeff (Peachpit Press, 2013)
The iPad is a game-changing product that reinvented the way we interact with digital content and the Web. Versitile, portable, powerful, ergonomically and functionally designed, it's the perfect companion for digital media. With Photos, music, movies, email, and hundreds of thousands of apps, the iPad helps you organize, explore, and maximize your digital world. Inexpensive and to-the-point, The iPad Pocket Guide is a complete companion to all the features and functions of the iPad including: Facetime, HD Video, Mail, Safari, Photos and Video, App Store, iBooks, Maps, Notes, Calendar, Contacts, and more. It will help you get up-and-running with easy to understand instructions and then show you hidden gems and tips to make you a true iPad expert.